Intragastric botulinum toxin injection directly regulates ghrelin expression via reactive oxygen species and NF-κB signaling - Lee, Chun-Te; Wang, Chung-Teng; Kuo, Hsin-Yu; Lee, Yinn-Lin; Chuang, Chiao-Hsiung; Hsu, Che-Wei; Ou, Horng-Yih; Wu, Hung-Tsung (Life sciences (1973), 2024)
One effective clinical strategy to combat obesity is intragastric botulinum toxin (BTX) injection, which increases gastric emptying time and regulates appetite. However, it remains unknown if and how BTX affects ghrelin levels. An obese animal model was established by feeding male mice with high-fat diet (HFD). BTX was administered by subserosal injection in the antrum via an upper midline laparotomy. The mice were monitored in terms of body weight and blood biochemical parameters. Glucose utility and insulin sensitivity were measured by intraperitoneal glucose and insulin tolerance tests. Additionally, stomach and liver were histologically examined after BTX treatment. AGS gastric adenocarcinoma cells were used to investigate the molecular mechanism by which BTX affects ghrelin expression. In HFD-fed mice, BTX injection significantly decreased both food intake and body weight over a 3-week monitoring period. Moreover, HFD-induced hyperglycemia, hyperinsulinemia, dyslipidemia and obesity readouts were improved after BTX injection. Importantly, mice also exhibited decreased plasma and gastric ghrelin levels after BTX injection. In cultured AGS cells, BTX significantly increased reactive oxygen species (ROS) levels and activated nuclear factor-κB (NF-κB), which led to decreased ghrelin expression. Pre-treatment with inhibitors of either ROS or NF-κB reversed the effects of BTX on ghrelin expression in the cultured cells. BTX decreases ghrelin expression in HFD-fed animals and in AGS cells through an ROS/NF-κB-dependent pathway. This mechanism may contribute to decreased food intake in obese subjects receiving intragastric BTX injection for weight control.